2006
DOI: 10.1016/j.brainres.2006.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and information processing variability predicts memory decrements associated with normal age-related cognitive decline and Alzheimer's disease (AD)

Abstract: Recent theoretical models of cognitive aging have implicated increased intra-individual variability as a critical marker of decline. The current study examined electrophysiological and information processing variability and memory performance in normal younger and older controls, and older adults with Alzheimer's disease (AD). It was hypothesized that higher levels of variability would be indicative of age-related and disease-related memory deficits. Results indicated both implicit and explicit memory deficits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 78 publications
3
20
1
Order By: Relevance
“…The main finding of a dynamic influence of variability on mean cognitive performance levels is consistent with findings indicating that cognitive variability predicts chronological age (e.g., Hultsch et al, 2002), cognitive functioning (e.g., Hultsch et al, 2000), and disease status (e.g., Fuentes et al, 2001;Hogan et al, 2006;see Hultsch & MacDonald, 2004;MacDonald et al, 2006, for reviews) independently of central tendency. However, the finding is inconsistent with recent results reported by Salthouse and Berish (2005).…”
Section: Discussionsupporting
confidence: 83%
“…The main finding of a dynamic influence of variability on mean cognitive performance levels is consistent with findings indicating that cognitive variability predicts chronological age (e.g., Hultsch et al, 2002), cognitive functioning (e.g., Hultsch et al, 2000), and disease status (e.g., Fuentes et al, 2001;Hogan et al, 2006;see Hultsch & MacDonald, 2004;MacDonald et al, 2006, for reviews) independently of central tendency. However, the finding is inconsistent with recent results reported by Salthouse and Berish (2005).…”
Section: Discussionsupporting
confidence: 83%
“…The task was based on a modified version of Hogan et al (2006). The task specification are outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…Of particular clinical relevance, older adults Neuromodulation of cognitive aging Li and Rieckmann 151 who exhibited more short-term moment-to-moment RT fluctuations showed steeper longitudinal declines over 13 years in the category fluency task that, in part, demands executive control [42]. Moreover, psychophysiological measures of neuronal variability during executive control that are derived from electroencephalogram (EEG), such as greater amplitude variability of the P300 evoked brain potential [43] or lower theta inter-trial phase coherence [44], showed increased variability in older adults and AD patients as compared to healthy controls. A lower level of EEG phase coherence across trials partly reflects temporal 'jitters' in neuronal activity, which is in turn associated with higher trial-to-trial RT fluctuation at the performance level (Figure 3c).…”
Section: Aging Of Information Processing Fidelitymentioning
confidence: 99%